2021
DOI: 10.2196/26236
|View full text |Cite
|
Sign up to set email alerts
|

Functionalities and Issues in the Implementation of Personal Health Records: Systematic Review

Abstract: Background Functionalities of personal health record (PHR) are evolving, and continued discussions about PHR functionalities need to be performed to keep it up-to-date. Technological issues such as nonfunctional requirements should also be discussed in the implementation of PHR. Objective This study systematically reviewed the main functionalities and issues in implementing the PHR. Methods This systematic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 115 publications
(699 reference statements)
0
26
0
Order By: Relevance
“…The absence of established provincial standards for interoperability between systems hampered the integration of electronic PCMs in team-based care. In a review of personal health record functionalities and implementation, Harahap et al [ 44 ] identified interoperability as a key implementation issue, as well as security and privacy, usability, data quality, and personalization as other important factors. Digital health transformation at the system level is needed to realize interoperability, providing standard definitions for data exchange and cooperation with the patient, provider, and organizational systems.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of established provincial standards for interoperability between systems hampered the integration of electronic PCMs in team-based care. In a review of personal health record functionalities and implementation, Harahap et al [ 44 ] identified interoperability as a key implementation issue, as well as security and privacy, usability, data quality, and personalization as other important factors. Digital health transformation at the system level is needed to realize interoperability, providing standard definitions for data exchange and cooperation with the patient, provider, and organizational systems.…”
Section: Discussionmentioning
confidence: 99%
“…Peffers et al [ 20 ] describe 6 activity-based methodologies for DSR, whereas Hevner et al [ 18 ] define 7 guidelines for DSR. This study follows the DSR guidelines defined by Hevner et al [ 18 ], which are grouped into 3 cycles or phases comprising the relevance cycle (identifying problems and the artifact type), design cycle (developing and evaluating the artifact), and rigor cycle (research contribution and communication; Figure 1 [ 5 ]). These guidelines have been followed by DSR studies in low- and middle-income countries to develop health information systems such as mobile health (mHealth) [ 19 , 21 - 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…A previous review on the implementation of PHRs shows that PHR research has mainly been conducted in high-income countries rather than in low- and middle-income countries [ 5 ]. Few studies that have been conducted in low- and middle-income countries aim to propose PHR applications for certain purposes, such as pediatric vaccination [ 6 ], or specific diseases, such as metabolic syndrome management [ 7 ], chronic heart failure [ 8 ], and kidney transplant [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the IN.2 of the PHR-S FM framework, a PHR system must support standards-based interoperability for seamless sharing of information between PHRs and other internal or external systems [ 48 ]. The same has been addressed in this study.…”
Section: Methodsmentioning
confidence: 99%